Selecting inflation indicators under an inflation targeting regime: evidence from the MCL method - Juha-Pekka Koskinen; Tuuli Koivu; Abdur Chowdhury (Bank of Finland, Institute for Economies in Transition (BOFIT), 2004)
This paper seeks to fill a gap in the literature by analyzing inflation in Poland, one of only two transition economies that have adopted a strict inflation-targeting policy.The paper also introduces a new method for selecting inflation indicators. Consistent with the earlier literature, empirical results find a strong link between the producer price index and consumer price index in Poland.This shows the importance of the manufacturing sector in determining the price level in the country.Overall, wages, broad money supply and the exchange rate are good indicators of inflation.
URN:NBN:fi:bof-201408072184
Keywords: 330; inflation; Poland; MCL method